1997
DOI: 10.1038/bjc.1997.330
|View full text |Cite
|
Sign up to set email alerts
|

Gossypol inhibition of mitosis, cyclin D1 and Rb protein in human mammary cancer cells and cyclin-D1 transfected human fibrosarcoma cells

Abstract: Summary The antiproliferative effects of gossypol on human MCF-7 mammary cancer cells and cyclin Dl-transfected HT-1060 human fibrosarcoma cells were investigated by cell cycle analysis and effects on the cell cycle regulatory proteins Rb and cyclin Dl. Flow cytometry of MCF-7 cells at 24 h indicated that 10 gm gossypol inhibited DNA synthesis by producing a G,/S block. Western blot analysis using antihuman Rb antibodies and anti-human cyclin Dl antibodies in MCF-7 cells and high-and low-expression cyclin Dl-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 26 publications
1
33
0
Order By: Relevance
“…Tumour volumes were measured every 3 days using a calliper and calculated according to the formula (L × W 2 )/2, where L and W are length and width, respectively [14]. When the tumours reached an appropriate size (200-250 mm 3 ), the mice were randomized into four groups of 10 mice and then treated with either (-)-gossypol (2.5, 5.0 or 10.0 mg kg -1 i.p. q.d) or DMSO (vehicle) for 7 days.…”
Section: Tumour Model In Nude Micementioning
confidence: 99%
See 1 more Smart Citation
“…Tumour volumes were measured every 3 days using a calliper and calculated according to the formula (L × W 2 )/2, where L and W are length and width, respectively [14]. When the tumours reached an appropriate size (200-250 mm 3 ), the mice were randomized into four groups of 10 mice and then treated with either (-)-gossypol (2.5, 5.0 or 10.0 mg kg -1 i.p. q.d) or DMSO (vehicle) for 7 days.…”
Section: Tumour Model In Nude Micementioning
confidence: 99%
“…Recent studies have focused on 391 npg the proapoptotic activity of (-)-gossypol. Previously, research on gossypol in relation to cancer has focused mainly on the antiproliferative activity of (±)-gossypol in a variety of cancers in vitro and in vivo, including breast [3], bladder [4], pancreas [5], lung [6], colon [1] and prostate [7] and cancers of the head and neck [8,9]. These anticancer effects have been attributed to the (-)-enantiomer, which is a more potent inhibitor of cancer cell growth [10].…”
Section: Introductionmentioning
confidence: 99%
“…CCND1 forms a holoenzyme with a cyclin-dependent kinase (CDK), either CDK4 or CDK6 that phosphorylates the retinoblastoma gene product of pRb. Since the phosphorylation of pRb results in the release of E2F transcription factors, freeing them to stimulate transcription of growthpromoting target genes, over-expression of CCND1 promotes tumor progression through the G1 phase of cell cycle in cells grown on a substratum [5,6] . Overexpression of CCND1 has been reported in a variety of human tumors including cancers of the lung, head, neck, and bladder [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Ligueros et al demonstrated that GP arrested the cell cycle at G1/S phase by decreasing Rb expression, Rb phosphorylation, and cycle D1 protein expression in human MCF-7 breast cancer cells (8). Thus, we aimed to determine whether GP affects the expression of cell cycle-regulated proteins, such as Cdk4, cyclin D1, Rb and phospho-Rb in MAT-LyLu cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that GP inhibits the proliferation of many human cancer cells in vitro and in vivo (5)(6)(7)(8)(9)(10). For example, GP significantly inhibited the growth of PC-3, DU-145, MCF-7 cells (6,(8)(9)(10) as well as the in vivo growth and metastasis of prostate cancer MAT-LyLu cells after implantation into Copenhagen rats (5). GP induces cell cycle arrest at G0/G1 phase in human prostate cancer PC-3 cells (6) or induces apoptosis in PC-3 (11) and colon cancer HT-29 cells (12).…”
Section: Introductionmentioning
confidence: 99%